Exploring the Role of mRNA Methylation in Insect Biology and Resistance - Jiayang Zhang; Luobin Lin; Botian Huang; Huoxi Liu; Huaqin Li; Wenmei Wu (Insects)
RNA methylation, characterized by modifications such as N6-methyladenosine, 5-methylcytosine, and N1-methyladenosine plays a crucial role in post-transcriptional gene regulation across diverse biological systems. While research on RNA methylation has predominantly focused on mammals, particularly its roles in epigenetic regulation and cancer biology, recent studies in insects have begun to explore their extensive functions in insect physiology. This review examines the mechanisms by which RNA methylation regulates growth, development, reproduction, environmental adaptation, and immune response in insects, providing insights into the biological characteristics of these organisms without prematurely speculating on pest control strategies. It aims to offer valuable insights into the role of RNA methylation in insect biology and resistance.